Effect of hot water dip treatment on postharvest anthracnose of banana var. Berangan - Mirshekari, Amin; Ding, Phebe; Kadir, Jugah; Mohd Ghazali, Hasanah (Academic Journals, 2012)
Heat treatment becomes a feasible method for controlling of postharvest decay in many freshly harvested commodities. Anthracnose is the main disease affecting the quality of banana fruits during export and marketing. In this study inoculated Berangan banana with Colletotrichum musae was dipped in hot water at 50°C for 0, 10, 20 min with or without fungicide, respectively. The disease development was determined by measuring the anthracnose infected areas after 10 days of treatment. There was a significant difference in size of lesion on Berangan banana as affected by different dipping time (0, 10 and 20 min) of hot water alone at 50°C. Anthracnose infection rating was reduced with increase dipping time. Dipping fruit in hot water at 50°C for 20 min was more effective in suppressing disease development as compared to hot water with fungicide as control (0 min). Conidia germination of C. musae was also assessed with hot water treatment at the same time-temperature combination with or without fungicide as previous. In general, conidia germination rate increases with increasing incubation time, while increasing the hot water dipping time with or without fungicide suppressed conidia germination with varying incubation times. There was a significant difference between hot water treatment alone and with fungicide for 0 min as control. Hot water dip for 10 and 20 min at 50 ºC inhibited conidia germination (100 %) of C. musae better than application of fungicide alone (55.92 %). It is suggested hot water dip treatment at 50 ºC for 20 min could be used to anthracnose in Berangan banana instead of using fungicide as practically used in commercial now.